Sustainable Livelihood Strategies for Smallholder Coffee Farmers (A Case Study in Aceh Tengah) - Tjahjo Tri Hartono; Rahmat Pramulya; Mas Davino Sayaza; Rimun Wibowo; Almyanti Ningrum (Universitas Ibn Khaldun Bogor, 2023)
An inclusive coffee supply chain refers to a production and distribution system that involves various stakeholders, including small-scale farmers, in the process. Inclusivity, in this context, means ensuring the involvement of all actors in the chain, from farmers to consumers, with a focus on equality and empowerment. This research aims to advocate for responsible coffee production and consumption in a region crucial for biodiversity, namely Aceh Tengah District, while also promoting gender equality in all responsible business practices. Data were collected through literature reviews and direct interviews with stakeholders, ranging from corporate to local levels, and analyzed using Focus Group Discussion (FGD) analysis. The study revealed insights into the supply chain profile in Aceh Tengah, existing policy, institutional conditions, and processes, the vulnerability context of coffee farmers' livelihoods, the conditions of their livelihood assets, and sustainable livelihood strategies suitable for their needs and conditions. This research is expected to contribute to the creation of responsible coffee production and consumption and advocate for gender equality in responsible business practices within the coffee sector.